Prepregs for Temperature Resistant Composites - Haincová, Eliška; Hájková, Pavlína; Kohout, Jan (Materials (Basel, Switzerland), 2019)
In this paper, carbon fabric reinforced inorganic matrix composites were prepared. The inorganic matrix based on alkali activated aluminosilicate was used because of its resistance to fire and the temperatures up to 1000 °C. Influence of heat treatment of fabric, high temperature treatment of composite and preparation method on the mechanical properties and morphology of the composites were studied. The preparation of composites with the subsequent steps of impregnation, layering and curing of the composites was compared with the prepreg preparation method, which separates the impregnation of the reinforcement from the production of the composite. The SEM photographs show no differences in morphology between composites prepared from heat treated fabric and composites prepared from original fabrics. All four series of samples were comparatively saturated with matrix. Despite this, tensile properties of heat-treated fabric composites were negatively affected. While composites with heat-treated fabric reached the tensile strength up to 274 MPa, composites prepared without heat-treated fabric exhibited strengths higher than 336 MPa. Samples exposed to temperatures reaching 600 °C retained up to 40% of their original strength. The effect of composite preparation method on the tensile properties of the composites has not been proved.
Keywords: aluminosilicate matrix; temperature resistant; carbon fiber; composite; prepreg; tensile strength